How is Math Problem-Solving Skill in Terms of Learning Style? - Setiyowati, Nadiah; Aisyah, Nyimas; Susanti, Ely; Susanti, Elsa (Universitas PGRI Palembang, 2024)
Learning style is one of the critical factors influencing the development of problem-solving skill. This study aims to examine mathematical problem-solving abilities in relation to students' learning styles. The research involved 32 eleventh-grade students from SMAN Banyuasin III. Data were collected through problem-solving tests and learning style questionnaires. A qualitative analysis was conducted to evaluate the students' problem-solving skills based on their learning styles. The findings revealed significant variations in problem-solving skills among the different learning style groups. Students with a visual learning style performed better on geometry problem-solving tasks, particularly when aided by visual elements. Conversely, auditory learners faced difficulties in comprehending the problems and often required additional verbal explanations from the teacher. Kinesthetic learners, however, struggled the most, exhibiting very low problem-solving abilities. These results underscore the importance of tailoring instructional strategies to accommodate diverse learning styles